2019
DOI: 10.1002/pssa.201900826
|View full text |Cite
|
Sign up to set email alerts
|

Multiferroic Properties and Magnetoelectric Coupling of Fe‐Doped (Ba0.7Ca0.3)TiO3‐Ba(Zr0.2Ti0.8)O3 Ceramics

Abstract: Fe-doped (Ba 0.7 Ca 0.3 )TiO 3 -Ba(Zr 0.2 Ti 0.8 )O 3 (BCZT) ceramics are prepared by a conventional solid-state reaction method, and their structure, multiferroic, and coupling properties are investigated. Ferromagnetism and magnetoelectric coupling are successfully realized by Fe 3þ doping. Meanwhile, Fe 3þ doping in BCZT results in a gradual transition from typical ferroelectrics to relaxor ferroelectrics or even quantum paraelectrics. In consequence, obvious magnetodielectric (MD) effect is observed only a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 58 publications
3
5
1
Order By: Relevance
“…Moreover, the peak is broadened with increase in x , which is typical for a relaxor ferroelectric. The phase transition disappears for large Fe dopant concentration (curves 4 and 4a) in good agreement with the experimental data of Gong et al ( x = 0–0.4). BaFeO 3 is a pure magnetic material, and it shows no ferroelectric properties, P = 0.…”
Section: Numerical Results and Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, the peak is broadened with increase in x , which is typical for a relaxor ferroelectric. The phase transition disappears for large Fe dopant concentration (curves 4 and 4a) in good agreement with the experimental data of Gong et al ( x = 0–0.4). BaFeO 3 is a pure magnetic material, and it shows no ferroelectric properties, P = 0.…”
Section: Numerical Results and Discussionsupporting
confidence: 91%
“…Temperature dependence of the real part of the DC for BTO (bulk, curves 1-4; and NP with N ¼ 5 shells, curves 1a-4a) for different Fe-doping content x: x ¼ 0 (curves 1 and 1a); x ¼ 0.1 (curves 2 and 2a); x ¼ 0.4 (curves 3 and 3a); x ¼ 0.6 (curves 4 and 4a). concentration (curves 4 and 4a) in good agreement with the experimental data of Gong et al [18] (x ¼ 0-0.4). BaFeO 3 is a pure magnetic material, and it shows no ferroelectric properties, P ¼ 0.…”
Section: Numerical Results and Discussionsupporting
confidence: 89%
“…This lead-free ceramic possesses a broad frequency-dependent peak corresponding to the temperature-dependent dielectric susceptibility, lower remnant polarization, and slimmer hysteresis loops due to the relaxor ferroelectric nanodomains, which are essential for realizing extremely high energy densities and efficiencies. [14][15][16][17] Moreover, it was reported that BCZT ceramics possess low dielectric loss (tan d) (1-3%), which is encouraging for obtaining high-efficiency energy storage density. 10,[18][19][20][21] BCZT relaxor ferroelectric ceramics have been attracting much attention for energy storage applications and electrocaloric cooling devices owing to their outstanding dielectric and ferroelectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…S3(a)-(c) of the ESI, † respectively show the SEM morphology of BCZT ceramics sintered at 1200 1C, 0.4BCZT-0.6ST ceramics sintered at 1200 1C, and 0.4BCZT-0.6ST ceramics sintered with the two-step sintering method, where 3 mol% MnO 2 is added as a sintering aid. Compared with the pure BCZT ceramics without sintering aid, 30 the addition of MnO 2 decreases the average grain size from 8 mm to 3.37 mm (Fig. S3(d method is adopted for the (1 À x)BCZT-xST (x Z 0.6) ceramics and a dense and fine grain morphology is obtained (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A uniform and dense microstructure without porosity is observed for all the ceramics.Fig.S3(a)-(c) of the ESI, † respectively show the SEM morphology of BCZT ceramics sintered at 1200 1C, 0.4BCZT-0.6ST ceramics sintered at 1200 1C, and 0.4BCZT-0.6ST ceramics sintered with the two-step sintering method, where 3 mol% MnO 2 is added as a sintering aid. Compared with the pure BCZT ceramics without sintering aid,30 the addition of MnO 2 decreases the average grain size from 8 mm to 3.37 mm (Fig.S3(d), ESI †) and lowers the sintering temperature from 1450 1C to 1200 1C, indicating the effect of the sintering aid MnO 2 on the nucleation and growth of BCZT as well as the grain refinement. Moreover, the introduction of ST further reduces the grain size to about 0.47 mm (Fig.…”
mentioning
confidence: 98%